Pelatihan Pengembangan Filling Roti dari Hasil Laut Sebagai Usaha Peningkatan Teaching Factory Smk Negeri 3 Probolinggo - Devi, Mazarina; Soekopitojo, Soenar; Hidayati, Laili (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2023)
Teaching Factory aims to transfer a real production or manufacturing environment into the classroom. Real-life production sites are used for teaching purposes to enhance teaching activities with existing knowledge of everyday industrial practice processes. The teaching factory at SMK Negeri 3 Probolinggo still experiences shortages, including skilled human resources in the field of bread processing and students who are less active in taking part in practicums in bakery subjects. Training on developing fillings from marine products as a development of contemporary bakery products by exploring local wisdom food sources is expected to be a solution to the problems found in the teaching factory program at SMK Negeri 3 Probolinggo. It is hoped that processing products from local food ingredients can produce bread products that are characteristic of bakery products at SMK Negeri 3 Probolinggo. The training that will be provided, apart from developing bakery products, will also provide training on making seafood floss from marine sources to fill several bakery products. The bread filling is made from seafood because Probolinggo is in the North Sea. After providing materials for making fish floss and bread, participants then prepared the materials and tools needed. The preparation of materials and tools greatly influences the effectiveness of the practice so that practice participants are very careful in preparing materials and practice tools. From the practical results, the leaders, and teachers of the culinary arts study program at SMK Negeri 3 Probolionggo are interested in making fish floss a superior product that will be developed in the teaching factory program at SMK Negeri 3 Probolinggo. Teaching Factory bertujuan untuk mentransfer lingkungan produksi atau manufaktur yang sebenarnya ke dalam kelas. Situs produksi kehidupan nyata digunakan untuk tujuan pengajaran dalam rangka meningkatkan kegiatan mengajar dengan pengetahuan yang ada di proses praktik industri sehari-hari. Teaching factory yang terdapat di SMK Negeri 3 Probolinggi masih mengalami kekurangan diantaranya adalah sumber daya manusia yang terampil di bidangn pengolahan roti serta siswa yang kurang aktif mengikuti praktium pada mata pelajaran bakery. Pelatihan pengembangan filling dari hasil laut sebagai pengembangan produk bakery kontemporer dengan menggali sumber pangan kearifan lokal diharapkan dapat menjadi pemecahan masalah yang terdapat pada program teaching factory di SMK Negeri 3 Probolinggo. Pengolahan produk dari bahan pangan lokal diharapkan dapat menghasilkan produk roti yang menjadi ciri khas produk bakery di SMK Negeri 3 Probolinggo. Pelatihan yang akan diberikan, selain pengembangan produk bakery juga akan memberikan pelatihan pembuatan abon seafood dari sumber hasil laut untuk mengisi beberapa produk bakery. Bahan isi roti dari hasil laut karena Probolinggo terletak di perairan laut Utara. Setelah pemberian materi pembuatan abon ikan dan roti, kemudian peserta menyiapkan bahan dan alat yang dibutuhkan. Persiapan bahan dan alat sangat mempengaruhi efektivitas jalannya praktik sehingga peserta praktik sangat teliti menyiapkan bahan dan alat praktik. Dari hasil praktik, pimpinan dan guru prodi tata boga SMK Negeri 3 Probolionggo tertarik untuk menjadikan abon ikan sebagai unggulan yang akan dikembangkan pada program teaching factory SMK Negeri 3 Probolinggo.